Dynamic Behavior of Fault Slip Induced by Stress Waves - Guang-an Zhu; Lin-ming Dou; Yang Liu; Zhen-guo Su; Hui Li; Yong Kong; Zhen-lei Li (Shock and Vibration, 2016)
Fault slip burst is a serious dynamic hazard in coal mining. A static and dynamic analysis for fault slip was performed to assess the risk of rock burst. A numerical model FLAC3D was established to understand the stress state and mechanical responses of fault rock system. The results obtained from the analysis show that the dynamic behavior of fault slip induced by stress waves is significantly affected by mining depth, as well as dynamic disturbance intensity and the distance between the stope and the fault. The isolation effect of the fault is also discussed based on the numerical results with the fault angle appearing to have the strongest influence on peak vertical stress and velocity induced by dynamic disturbance. By taking these risks into account, a stress-relief technology using break-tip blast was used for fault slip burst control. This technique is able to reduce the stress concentration and increase the attenuation of dynamic load by fracturing the structure of coal and rock. The adoption of this stress-relief method leads to an effective reduction of fault slip induced rock burst (FSIRB) occurrence.